Written Finnish: Genuine vernacular or something completely different? Kirjalik soome keel: kas ehe rahvakeel või midagi hoopis muud? - Häkkinen, Kaisa (Foundation Kultuurileht, 2026)
The first Estonian book was printed 500 years ago; no copies of the book have survived. The history of publishing in Finnish dates to 1543, with Mikael Agricola’s Abc-book. Agricola went on to publish eight additional works. This development was driven by the Lutheran Reformation on both sides of the Gulf of Finland. This article discusses the reasons why the paths of development diverged so markedly between the sister languages Finnish and Estonian. Finland was part of Sweden, but remained geographically distinct. A Swedishspeaking population lived along the coast, but these were ordinary peasants like their Finnish neighbours rather than a social upper class. Estonia, in contrast, had a German-speaking minority that was permanently present throughout the country as a dominant force. The clergy was also German-speaking. Finland formed a single diocese in the Church of Sweden. From the early 14thcentury onward, most bishops of Turku were born in Finland and spoke Finnish as their mother tongue. Local parish communities likely preferred priests with whom they could communicate in their own language. Swedish was not described as an official or socially superior language by Sebastian Münster in his Cosmographia (1544) Although scholars writing in Finnish knew the language, the literary register was different from everyday speech. Almost all texts were word for word translations from other languages, such as Latin, German, or Swedish. In a sense, the old literary Finnish was colonized from within by Finns themselves: Sweden had not yet had time to develop a strong national identity or sense of superiority, often combined with linguistic colonialism. Swedish-speaking administrators did thus not interfere with how Finns used their own language, but rather encouraged Finns to use pure Finnish. In the 19thcentury, in the spirit of national awakening, the language was thoroughly reformed in terms of both vocabulary and grammar. When Finland declared independence in 1917, the state of the language was strong and stable. Today, however, the situation is shifting once again, as English is exerting more and more influence on everyday language use. It appears that Finns are once more adopting a foreign model at the expense of their own language.